All-solid-state carbon-nanotube-fiber-based finger-muscle and robotic gripper. Issue 1 (2nd January 2022) - Liu, Xia; Ji, Hua; Liu, Boyan; Yang, Qingsheng
ABSTRACT: Carbon nanotube fibers (CNTFs) have many desirable properties such as lightweight, high strength, high conductivity, and long lifetimes. Coiled CNTF is an ideal material for preparing electrochemically driven artificial muscles. While previous studies focused mainly on the actuation performance of artificial muscles made of CNTF, this study focuses on an actuator that mimics human finger movements (flexion). More specifically, the preparation of CNTF muscles were optimized by twisting with weight. Then, actuators are designed and assembled by combining all-solid-state CNTF muscles with polypropylene (PP) sheets. Moreover, a dual-electrode system, which is infiltrated by a gel electrolyte, is built into the muscle actuator. In addition, a robotic gripper is fabricated, which uses these actuators. This study can help improve the design of CNTF-based muscle-actuators and future applications in robotics. GRAPHICAL ABSTRACT: uf0001